Analisis Sistem Informasi Manajemen Berbasis Teknologi di MTS YPAK Cigugur - Ujang Saepul Milah; Wulandari Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
The purpose of this study was to analyze the management information system used in MTS YPAK Cigugur. The method applied in this study is qualitative descriptive analysis. Data collection techniques were carried out by interviewing the operator staff of MTS YPAK Cigugur. In addition, the researcher also conducted a literature study on a number of scientific journals related to the topic to be analyzed. The results of the study indicate that the management information system has been implemented well in MTS YPAK Cigugur. The management information system model used in MTS YPAK Cigugur is the education management information system or EMIS developed by the Ministry of Religion to assist Islamic educational institutions in managing data related to student data, educator and education data, facilities and infrastructure, and other institutional interest data. In its implementation, there are various aspects that influence it, including the procurement of adequate software such as computers and laptops, the availability of software for data processing and adequate networks to support the smooth running of the data processing process, and human resources as users who are capable and understand technology-based management information systems.